Mutation Spectrum of Cancer-Associated Genes in Patients With Early Onset of Colorectal Cancer - Zhunussova, Gulnur; Afonin, Georgiy; Abdikerim, Saltanat; Jumanov, Abai; Perfilyeva, Anastassiya; Kaidarova, Dilyara; Djansugurova, Leyla (Frontiers in Oncology, 2019)
Background: Colorectal cancer (CRC) has a rising incidence worldwide, as well as in the Republic of Kazakhstan, and is growing younger. Hereditary forms associated with the development of colon and rectal cancer and early-onset CRC have never been studied in the population of Kazakhstan. The aim of this research was the investigation of the spectrum of CRC-related gene mutations to determine the mutations causing early onset of CRC in the Kazakhstan population. Methods: The study included 125 unrelated patients from Kazakhstan (range 17-50 years) with early onset CRC. Genomic DNA was obtained from peripheral blood of the patients. Next-generation sequencing was performed using TruSightCancer Kit on the MiSeq platform. Studio Variant was used to annotate and interpret genetic variants. Results: Bioinformatics analysis of Next-generation sequencing data has revealed 11152 variants of 85 genes, of them, 3,790 missense, 6,254 synonymous variants, 44 3’UTR variants, 10 frameshift variants, 5 stop-gain variants, 4 in-frame deletions, 2 splice donor, 1 splice acceptor variant, and 1042 intron or non-coding variants. APC, BRCA2/1, ALK, BRIP1, EGFR, FANCA, FANCD2, FANCI, HNF1A, MEN1, NSD1, PMS2, RECQL4, RET, SLX4, WRN, and XPC genes mutated most often. According to the ACMG guidelines and LOVD/ClinVar databases, 24 variants were pathogenic (10 frameshifts, 5 missenses, 5 stop-gain, 1 in-frame deletion, and 3 splice-site mutations), and 289 were VUS with population frequency <1%, 131 of them were attributed to deleterious. In the study, 50% of all pathogenic mutations found in Kazakhstani patients with early CRC onset were identified in the subgroups with a family history of CRC and primary multiple tumors. In APC, pathogenic mutations were most often (21%). Conclusion: Pathogenic and likely pathogenic mutations were found in 20 (16%) out of 125 patients. Eight novel pathogenic mutations detected in FANCI, APC, BMPR1, ATM, and DICER1 genes have not been reported in the literature earlier. Given the high frequency and wide spectrum of mutations, NGS analysis must be carried out in families with a history of CRC/CRC-related cancers with the purpose to identify cause-effective mutations, clarify the clinical diagnosis, and prevent the development of disease in family members.